2015
DOI: 10.3389/fonc.2015.00185
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Review of CyberKnife Stereotactic Body Radiotherapy for Adrenal Tumors (Primary and Metastatic): Winthrop University Hospital Experience

Abstract: The adrenal gland is a common site of cancer metastasis. Surgery remains a mainstay of treatment for solitary adrenal metastasis. For patients who cannot undergo surgery, radiation is an alternative option. Stereotactic body radiotherapy (SBRT) is an ablative treatment option allowing larger doses to be delivered over a shorter period of time. In this study, we report on our experience with the use of SBRT to treat adrenal metastases using CyberKnife technology. We retrospectively reviewed the Winthrop Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…On the contrary, active motion management strategies like gating and tracking, allow for real-time target monitoring during radiotherapy [22,45]. When applying gating or tracking, the ITV-concept is no longer needed and PTV sizes can be substantially decreased.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, active motion management strategies like gating and tracking, allow for real-time target monitoring during radiotherapy [22,45]. When applying gating or tracking, the ITV-concept is no longer needed and PTV sizes can be substantially decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Porte et al (31) have also reported that the median survival time is 11 months with 3 of 43 NSCLC patients having survival time of more than 5 years after resection of isolated adrenal metastasis. Compared to surgical resection, conventional external beam radiotherapy has been considered as unreliable for the management of solitary adrenal metastases because treatment responses are typically transient and incomplete (32). Soejima et al (33) have reported a survival time of 6 months in a study of 14 patients with adrenal metastases receiving radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, growing evidences have supported that stereotactic body radiotherapy (SBRT) is a safe, non-invasive, and effective technology, showing high local control (LC) rate and low incidence of complication in selected metastatic patients, especially when surgery is not allowed or refused567. It is defined by the American Society of Radiation Oncology as external-beam radiotherapy used to precisely deliver high doses of radiation to an extracranial target within the body, either as a single dose or a small limited number of radiation fractions8.…”
mentioning
confidence: 99%